The impact of rewards on the success of crowdfunding campaigns - Ramos, Pedro Costa Custódio da Silva (2014)
This study analyses crowdfunding, a recent method of collecting money relying on as many people as possible, being these ones able to donate as little as one dollar. With the positive evolution of crowdfunding’s reach and funds raised it is crucial to take a look at what has been done so far and how can one improve these results. The investigation performed here focused on non-financial rewards, which are gifts donors may get in exchange for making a donation, and how could these enlarge the total amount collected by campaign creators. Based on a database and an experiment, findings point out that there is a significant positive relationship between the number of rewards and the money collected. Furthermore, the lower the standard deviation of the price of rewards within a single campaign, the higher the money collected.